Hand hygiene among health care workers - Mani Ameet; Shubangi A; Saini Rajiv (Wolters Kluwer Medknow Publications, 2010)
Healthcare-associated infections are an important cause of morbidity and mortality among hospitalized patients worldwide. Transmission of health care associated pathogens generally occurs via the contaminated hands of health care workers. Hand hygiene has long been considered one of the most important infection control measures to prevent health care-associated infections. For generations, hand washing with soap and water has been considered a measure of personal hygiene. As early as 1822, a French pharmacist demonstrated that solutions containing chlorides of lime or soda could eradicate the foul odor associated with human corpses and that such solutions could be used as disinfectants and antiseptics. This paper provides a comprehensive review of data regarding hand washing and hand antisepsis in healthcare settings. In addition, it provides specific recommendations to uphold improved hand-hygiene practices and reduce transmission of pathogenic microorganisms to patients and personnel in healthcare settings. This article also makes recommendations and suggests the significance of hand health hygiene in infection control.